Illustrative Handbook of General Surgery - Chen, Herbert; SpringerLink (Online service) (London : Springer London, 2010)
The Illustrative Handbook of General Surgery is a handy, compact atlas covering all facets of General Surgery. Extremely useful to carry around as a refresher guide before going into theater, the areas of surgery covered are: Endocrine surgery Breast surgery Esophageal and Gastric Surgery Small Bowel and Appendix Surgery Colorectal Surgery Anorectal Surgery Hernia Surgery Hepatobiliary Surgery Pancreatic Surgery Each chapter includes a brief narrative describing the procedure and several photographic illustrations as a quick visual aid to the reader. In addition, the authors outline common pitfalls and provide suggestions drawn from their extensive personal experiences. Dr Herbert Chen is Vice-Chairman of Research, Department of Surgery, Professor, Division of General Surgery and Chief of Endocrine Surgery at the University of Wisconsin, USA.
Section 1 Endocrine Surgery -- Total Thyroidectomy and Thyroid Lobectomy -- Central Neck Dissection -- Modified Radical Neck Dissection -- Parathyroidectomy -- Open Adrenalectomy -- Laparoscopic Adrenalectomy -- Section 2 Breast Surgery -- Breast Biopsy -- Breast Procedures -- Axillary Procedures -- Section 3 Esophageal and Gastric Surgery -- Laparoscopic Nissen Fundoplication -- Laparoscopic Paraesophageal Hernia Repair -- Minimally Invasive Surgical Treatment of Achalasia -- Laparoscopic Roux-en-Y Gastric Bypass -- Esophagectomy -- Gastric Resection -- Section 4 Small Bowel and Appendix Surgery -- Small Bowel Resection -- Meckel$1 (Bs Diverticulum Resection -- Appendectomy -- Section 5 Colorectal Surgery -- Right Hemicolectomy -- Sigmoid Colectomy -- Low Anterior Resection and Abdominoperineal Resection -- Stomas (Colostomy and Ileostomy) -- Section 6 Anorectal Surgery -- Lateral Internal Sphincterotomy -- Cryptoglandular Disease -- Pilonidal Operations -- Hemorrhoids -- Section 7 Hernia Surgery -- Abdominal Wall Hernias: Introduction -- Inguinal Herniorrhaphy -- Totally Extraperitoneal Preperitoneal Laparoscopic Inguinal Hernia Repair -- Incisional Hernia -- Umbilical Hernia -- Section 8 Hepatobiliary Surgery -- Hepatic Procedures -- Biliary Procedures -- Laparoscopic Splenectomy -- Section 9 Pancreatic Surgery -- Pancreaticoduodenectomy (Whipple Procedure) -- Distal Pancreatectomy -- Surgical Treatment of Chronic Pancreatitis.s
Keywords: Medicine; Radiology, Medical; Critical care medicine; Surgery; Endoscopic surgery; Medicine & Public Health; Surgery; General Surgery; Minimally Invasive Surgery; Imaging / Radiology; Intensive / Critical Care Medicine